Epileptiform EEG Discharges and Risk of Epilepsy Following Febrile Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Kangnam and Masan Samsung Changwon Hospitals, Korea, studied the relation between epileptiform discharges on the EEG after febrile seizures (FS) and the risk of developing epilepsy and recurrence of FS.